Postoperative infection mycobacterium abscessus associated with liposuction and autologous fat grafting: A narrative review - Hoang, Thanh Tuan; Nguyen, Van Luat; Nguyen, Anh Ngoc; Luu, Dang Ai (Tạp chí Y học Thảm hoạ và Bỏng, 2023)
Liposuction and autologous fat grafting are common aesthetic procedures these days. Although these procedures are relatively safe, some severe complications sometimes happen affecting aesthetic results and the patient’s quality of life. Postoperative infection of Mycobacterium abscessus after liposuction and autologous fat grafting is an uncommon complication along with untypical symptoms. This results in misdiagnosis and delays in proper diagnosis and treatments, prolonging the treatment period. This narrative review summarises cases of M. abscessus infection associated with liposuction and autologous fat grafting, then presents causes, diagnoses, preventive care, and treatments of such cases. This aims to enhance the awareness of this infection after aesthetic surgery and contributes to the appropriate prevention and treatment.